Studi meta analisis: Efektivitas terapi menulis dalam menurunkan kecemasan orang dewasa dengan pengalaman traumatis - Putu Nitya Sarahdevina; Ananta Yudiarso (University of Muhammadiyah Malang, 2022)
Anxiety is often experienced by adults who have a less pleasant life experience. Writing therapy is an intervention that adults can use to express anxiety. This study aims to find out the effectiveness of writing therapy in lowering anxiety levels. The study used a meta-analysis method through a literature review of 14 research articles corresponding to research variables. The total number of participants in the study was 1,593. Data is analyzed by adjusting the effect size. The analysis results in effect size value obtained from fixed effects are -0.06 (95% Cl = -0.167 to 0.042, P =0.2434) and I² (inconsistency) by 66.9%, which means that writing therapy has little effect in lowering anxiety levels. Writing therapy has little effect on decreasing anxiety levels. Writing therapy can be given in conjunction with other interventions in order to provide more optimal effects